Clinical observation of an HIV-infected patient heterozygous for the mutant allele of the CCR5 del 32 chemokine receptor - Z. I. Akhmedjanova; D. M. Urunova; M. V. Zalyalieva (Журнал инфектологии)
The article describes the clinical observation of an HIVinfected patient heterozygous for the mutant allele of the CCR5 del 32 chemokine receptor, who is not receiving antiretroviral therapy. The follow-up showed the course of the disease over 20 years of follow-up, without receiving antiretroviral therapy, with a gradual decrease in the number of CD4-lymphocytes and an increase in viral load.